FEASIBILITY ANALYSIS OF FACTORS THAT INFLUENCE PRODUCTION IN CABBAGE FARMING IN WANASABA SUBDISTRICT, EAST LOMBOKK DISTRICT - dandi sugiono (Journal of Agri Rinjani: Social Agricultural Economics - Faculty of Agriculture, UGR, 2023)
ABSTRACT Cabbage is a plant that is often planted in wetlands. In developing the Cabbage plant requires careful maintenance and incentives to obtain high yields. For this reason, cultivation techniques must be taken into account such as the use of superior varieties, the use of chemical fertilizers, pesticides, good processing. Increasing production yields can be done in several ways, one of which is by optimizing use of production factors to then be used effectively and efficiently. The production factors in question are land area, labor, seeds and fertilizer. Land area and labor factors play an important role in supporting the success of cabbage production. Land area and seeds are very important means of production. Proper and efficient planting and care of seeds will produce high production. In addition, the labor production factor together with other production factors, if used optimally and efficiently, will be able to increase production optimally. The objectives of this research are: 1. To find out the production factors that influence cabbage farming 2. To find out the level of use of the most efficient production factors in cabbage farming. This research was conducted in Wanasaba District, 2 villages were selected as sample areas using purposive sampling, namely Bebidas Village and Beririjarak Village with data analysis using production function analysis, namely the transformation form of the Cobb-Douglas function into linear logarithmic form. The results of the research show: the factors that have a real and significant influence on cabbage production are X1 land area, X2 Seeds X3 Fertilizer, and X5 Labor while the variable Keywords: farming, production, cabbage